Stream microbial communities and ecosystem functioning show complex responses to multiple stressors in wastewater. (3rd September 2020) - Burdon, Francis J.; Bai, Yaohui; Reyes, Marta; Tamminen, Manu; Staudacher, Philipp; Mangold, Simon; Singer, Heinz; Räsänen, Katja; Joss, Adriano; Tiegs, Scott D.; Jokela, Jukka; Eggen, Rik I. L.; et al.
Abstract: Multiple anthropogenic drivers are changing ecosystems globally, with a disproportionate and intensifying impact on freshwater habitats. A major impact of urbanization are inputs from wastewater treatment plants (WWTPs). Initially designed to reduce eutrophication and improve water quality, WWTPs increasingly release a multitude of micropollutants (MPs; i.e., synthetic chemicals) and microbes (including antibiotic‐resistant bacteria) to receiving environments. This pollution may have pervasive impacts on biodiversity and ecosystem services. Viewed through multiple lenses of macroecological and ecotoxicological theory, we combined field, flume, and laboratory experiments to determine the effects of wastewater (WW) on microbial communities and organic‐matter processing using a standardized decomposition assay. First, we conducted a mensurative experiment sampling 60 locations above and below WWTP discharges in 20 Swiss streams. Microbial respiration and decomposition rates were positively influenced by WW inputs via warming and nutrient enrichment, but with a notable exception: WW decreased the activation energy of decomposition, indicating a "slowing" of this fundamental ecosystem process in response to temperature. Second, next‐generation sequencing indicated that microbial community structure below WWTPs was altered, with significant compositional turnover, reduced richness, and evidence of negative MP influences. Third, a series of flume experiments confirmed that although diluted WW generally has positive influences on microbial‐mediated processes, the negative effects of MPs are "masked" by nutrient enrichment. Finally, transplant experiments suggested that WW‐borne microbes enhance decomposition rates. Taken together, our results affirm the multiple stressor paradigm by showing that different aspects of WW (warming, nutrients, microbes, and MPs) jointly influence ecosystem functioning in complex ways. Increased respiration rates below WWTPs potentially generate ecosystem "disservices" via greater carbon evasion from streams and rivers. However, toxic MP effects may fundamentally alter ecological scaling relationships, indicating the need for a rapprochement between ecotoxicological and macroecological perspectives. Abstract : Global change assessments have typically ignored synthetic chemical pollution, despite the rapid increase of pharmaceuticals, pesticides, and industrial chemicals in the environment. Inputs of treated municipal wastewater are a major source of synthetic chemicals in receiving aquatic ecosystems. We found that microbial activity and decomposition rates were positively influenced by the presence of treated effluent via warming and nutrient enrichment, despite negative effects of synthetic chemicals, leading to increased respiration and estimated carbon evasion in streams and rivers.